2020
DOI: 10.3390/ijerph17072583
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the Chronotypes and Eating Habits of Hong Kong School-Aged Children

Abstract: Later chronotypes have been found to be associated with unhealthy diets in adolescents and adults, but no study has been conducted in children. The aim of this study was to investigate the associations between the chronotypes and dietary patterns of school-aged children. Children aged 7–11 and their parents were recruited from five mainstream schools in Hong Kong. The parents were told to complete questionnaires on the children’s circadian preferences, food frequency, and dietary behaviors. All of the question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 59 publications
1
24
0
Order By: Relevance
“…Recent studies show the relationship between evening chronotype and increased nutritional deficiency risk in the community in school-age children (Arora and Taheri, 2015;Yu et al, 2020), adults (Maukonen et al, 2017) and young females (Al-Rethaiaa et al, 2010;Sato-Mito et al, 2011). In a study conducted with school-age children aged 7-11, individuals with evening-type boys skip breakfast more often; and individuals with evening-type girls consume fast food more frequently (Yu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies show the relationship between evening chronotype and increased nutritional deficiency risk in the community in school-age children (Arora and Taheri, 2015;Yu et al, 2020), adults (Maukonen et al, 2017) and young females (Al-Rethaiaa et al, 2010;Sato-Mito et al, 2011). In a study conducted with school-age children aged 7-11, individuals with evening-type boys skip breakfast more often; and individuals with evening-type girls consume fast food more frequently (Yu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show the relationship between evening chronotype and increased nutritional deficiency risk in the community in school-age children (Arora and Taheri, 2015;Yu et al, 2020), adults (Maukonen et al, 2017) and young females (Al-Rethaiaa et al, 2010;Sato-Mito et al, 2011). In a study conducted with school-age children aged 7-11, individuals with evening-type boys skip breakfast more often; and individuals with evening-type girls consume fast food more frequently (Yu et al, 2020). Another study conducted in young adolescents aged 11-13 years showed that unhealthy snack consumption, insufficient vegetable/fruit consumption and nighttime caffeine consumption are associated with the evening chronotype (Arora and Taheri, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Twelve of the included studies had a cross-sectional design [ 10 , 12 , 18 , 20 , 21 , 22 , 23 , 24 , 26 , 27 , 29 , 30 ], one was a retrospective cohort [ 28 ] and two were case-control [ 19 , 25 ]. Six out of the fifteen studies selected were conducted in Turkey and two in Spain.…”
Section: Resultsmentioning
confidence: 99%
“…1,3 During this transition, adolescents will shift from a morning chronotype, well described in pre-pubertal children with an early morning wake time and early bedtime, to an evening chronotype as they start to stay up later and sleep in later. 1,5,6 Adolescents ages 17 to 19 are on average the latest chronotypes, and their delayed sleep-wake behaviours clash with traditional eating patterns, school start times and other scheduled activities of daily living. [1][2][3] As the obesity epidemic continues to rise in adolescence, it becomes imperative to understand developmentally appropriate eating behaviours and to create weight management strategies that build on those innate patterns and preferences.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] It could be postulated that adherence may improve if dietary recommendations mirror an eating pattern that best fits with the usual weekly routine and chronotype. 1,4,6 One dietary intervention that is gaining in popularity is time limited eating (TLE) [16][17][18][19] TLE has been shown to be an effective pattern for weight loss and to improve glycaemic control in adults with obesity and type 2 diabetes (T2D). [20][21][22] Although this approach may align well with normal adolescent eating patterns, it has not been well studied in adolescents with obesity.…”
Section: Introductionmentioning
confidence: 99%